Speeding wheat breeding using super-long lighting and immature embryo culture in vitro - ZHENG Nannan; LU Xiangqian; ZHAO Junheng; FU Yujie; YE Lingzhen (浙江大学学报. 农业与生命科学版)
Wheat is relatively long from germination to seed maturity, and normally only one generation can be produced annually. Shortening the whole growth period, consequently producing seeds of multiple generations per year, is beneficial for improving wheat breeding efficiency. Low temperature (vernalization response) and light length (photoperiod response) are the two key factors affecting the processes of wheat growth and development, or the whole growth period. On the basis of the relevant characteristics, we conducted different photoperiod and low-temperature vernalization treatments on wheat plants with different growth habits. Through observations of the growth stages, we found that super-long lighting (22 h light/2 h darkness) significantly shortened the wheat growth period and had a compensatory vernalization effect. No significant differences in panicle length, number of effective tillers per plant, or thousand grain weight were detected between the super-long lighting treatment and the control (16 h light/8 h darkness). Immature embryo culture in vitro at different time after pollination revealed that the 12-day-old young embryo had a high germination rate. Accordingly, the combination of super-long lighting and immature embryo culture in vitro may obtain 6-7 and 3-4 generations per year for spring- and winter-habit wheats, respectively. In conclusion, the method of speeding breeding developed in this study can be used in wheat breeding programs to improve breeding efficiency.